Complex Gleason measures and the Nemytsky operator - Mariani, Maria C.; Tweneboah, Osei K.; Valles, Miguel A.; Bezdek, Pavel (Annales Mathematicae Silesianae, 2019)
This work is devoted to the generalization of previous results on Gleason measures to complex Gleason measures. We develop a functional calculus for complex measures in relation to the Nemytsky operator. Furthermore we present and discuss the interpretation of our results with applications in the field of quantum mechanics. Some concrete examples and further extensions of several theorems are also presented.